Effect of ammonia level and treatment temperature on intake and digestibility of wheat straw by lambs - A. Laytimi; K. Bolsen; B. Janicki (Kansas Agricultural Experiment Station Research Reports, 1984)
Replicate, covered wheat straw (WS) stacks were treated with 1.5 or 3.0% anhydrous ammonia in three environmental chambers at 37, 68, or 95 F, for 23 days. Then digestibility was measured (wethers). Rations were 88% wheat straw and 12% supplement. The control wheat straw was non-ammoniated but contained 5% urea in the supplement. Stack temperatures increased rapidly within 2.5 hours post-ammoniation, and equilibrated at chamber temperatures for the rest of the treatment period. Both crude protein (CP) and in vitro matter digestibility of the WS increased with ammonia level and treatment temperature. Percent of the ammonia recovered increased with temperature and was always higher with the low ammonia level treatment. Ammoniation improved ration intakes and dry matter digestibility, but did not increase CP digestibility which decreased as temperature increased. Ammoniation solubilized the hemicelluloses, cellulose, and lignin and increased the digestibility of the fiber components.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Ammonia; Temperature; Intake; Wheat straw; Digestibility